(untitled) (Journal of Parents and Teachers, 2014)
The question "How should we prepare our young people to live in society?" presents us, parents and educators, with the challenge of educating young people to be active, supportive, participative, etc. people. This implies that the work of integration into social life must take place within the family from an early age, as well as at school, since it is the school’s duty to prepare pupils for life. The following article offers the keys to the question, how should I guide my students towards the responsible exercise of citizenship? To do so, it suggests simple activities that promote participation and active involvement.